Faculty of Science - Miroslava Ruzickova (Communications - Scientific letters of the University of Zilina, 2003)
The history of the Faculty of Science is relatively short – the Faculty was established in August 1998 with an objective to complete the former mostly technically oriented education with courses in humanities. Although the first departments of the newly created Faculty were departments of mathematics, other departments were gradually established and currently there is a wide range of subjects that can be studied in bachelor’s or master’s programs and one subject also in a postgraduate program.Although there are several universities in Slovakia offering full degree programs in English Language and Literature and/or concentrating on training teachers there is a permanent shortage of qualified teachers of English. To improve the situation the management of the Faculty decided to design new five-year degree programs concentrating on training teachers of English and another subject, as for example, mathematics/information science/music/religious studies. Curricula and courses were thoroughly redesigned to meet new requirements and incorporate the experience of the rest of the world. The courses allow for the training of either primary school or secondary school teachers. The courses offered by the Faculty are diverse.